(untitled) (Journal of Bio-Science, 2011)
Context: Understanding the distribution of different groups of bacteria and their role in the hatchery production of catfishes is important for the implementing of appropriate disease control strategies and sustainable production. Objectives: The aim was to study the distribution of total viable bacteria, motile aeromonads, pseudomonads and oxytetracycline (OTC) resistant bacteria in Pangasius pangasius hatcheries of West Bengal, India. Materials and Methods: Following standard methods, quantification of total viable counts (TVCs) on tryptic soy agar (TSA), motile aeromonads on starch ampicillin agar, pseudomonads on Pseudomonas isolation agar and antibiotic resistant bacteria on TSA supplemented with OTC at 25-mg/ml was done from fertilized eggs, hatching pool water, larvae, larval rearing water and source water collected in three P. pangasius hatcheries in West Bengal, India. Results: The hatching pool water had high levels of TVCs and motile aeromonads than in source water. The magnitude of increase in the levels of TVCs and motile aeromonads in hatching pool water was to the tune of 2 to 3 log units than in source water. The mean counts of viable bacteria, motile aeromonads, pseudomonads and OTC resistant bacteria recorded on fertilized P. pangasius eggs were log5.48 ± 0.28 /egg, log4.11 ± 0.29 /egg, log3.32 ± 0.35 /egg and log4.50 ± 0.56 /egg, respectively. In larvae the counts were log6.58 ± 0.31 /g and log5.36 ± 0.23 /g, log4.34 ± 0.20 /g and log5.74 ± 0.22 /g respectively for viable bacteria, motile aeromonads, pseudomonads and OTC resistant bacteria. The OTC resistant bacteria were ranged from 0.91 to 24.29%, 5.12 to 22.67% and 11.49 to 20.83% of TVCs in water, eggs and larvae, respectively. Significant differences existed among the OTC resistant bacteria between eggs and larvae, and larval rearing water and larvae. Conclusion: The results of this study suggest that there is an urgent need on the prudent use of antibiotics in pangasid catfish hatcheries and to control the bacterial flora by other means. Key words: Catfish hatchery; Pangasius pangasius; Aeromonads; Pseudomonads; Oxytetracycline resistant bacteria DOI: 10.3329/jbs.v17i0.7094 J. bio-sci. 17: 13-20, 2009